2015
DOI: 10.3906/sag-1406-58
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between antibiotic resistance and virulence ofPseudomonas aeruginosa clinical isolates

Abstract: IntroductionThe increasing frequency of multidrug-resistant Pseudomonas aeruginosa (MDRPA) strains is concerning, as efficacious antimicrobial options are severely limited. Risk factors for MDRPA infection include prolonged hospitalization, exposure to antimicrobial therapy, and immunocompromised states such as human immunodeficiency virus infection. The emergence of MDRPA isolates during therapy was reported in 27%-72% of patients with initially susceptible P. aeruginosa isolates. Patients with severe MDRPA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 32 publications
2
14
1
Order By: Relevance
“…Also, Rossi Goncalves23 concluded a high rate of MDR (73.9%). However, a lower rate of MDR was reported in other studies conducted in Egypt 24,25. This high rate of resistance among our isolates may be due to the fact that they were from hospital-acquired infections 26…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Also, Rossi Goncalves23 concluded a high rate of MDR (73.9%). However, a lower rate of MDR was reported in other studies conducted in Egypt 24,25. This high rate of resistance among our isolates may be due to the fact that they were from hospital-acquired infections 26…”
Section: Discussioncontrasting
confidence: 53%
“…The rate of imipenem resistance varies widely from 1% to 73.5% 12,16,2325,27,28. In our study, the frequency of imipenem resistance in P. aeruginosa was 42.5%.…”
Section: Discussionsupporting
confidence: 41%
“…The subsequent important stage of our study was to verify the extent to which the antibiotics are able to influence the virulence genes of the UPEC strains. It has been long observed that antibiotic resistance correlates with certain bacterial features, this correlation is especially observed between fluoroquinolones and bacterial virulence [27,28,34,[61][62][63][64][65][66][67]. In our study, the presence of six virulence factor gene regions (papC, sfaE/D, cnf1, usp, fimG/ H, hlyA) and their expression were analyzed.…”
Section: Ciprofloxacin Induces the Loss Of The Virulence Factor Genesmentioning
confidence: 91%
“…1 Recently, multidrug-resistant bacteria have become more common and are causing problems in the treatment of infections. 2 It was found that the dissemination of resistance among bacteria has been attributed to inappropriate use of antimicrobials in hospitals and communities and failure among health care providers to comply with infection control precautions. 3 Klebsiella pneumoniae is an opportunistic pathogen that causes both hospital-acquired and community-acquired infections such as pneumonia, urinary tract infection, and pyogenic liver abscess.…”
Section: Introductionmentioning
confidence: 99%